2000
DOI: 10.1007/s002100000236
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, functional coupling and pharmacological characterization of the rat dopamine D 4 receptor

Abstract: It has been difficult to observe functional coupling of the D4 receptor to second messenger systems and a robust functional assay system for this receptor is still lacking. In the present study, the rat dopamine D4 receptor was cloned from rat retina. Sequence comparison revealed identity with the published sequence of Ashgari and co-workers, including the two amino acid insertions (V-Q) at position 92 which are not present in the published sequence of O'Malley and coworkers. The rat dopamine D4 receptor was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…6, C and D; Table 2), through a lower maximum response rather than a decrease in potency, which can be difficult to interpret. A similar discrepancy has been reported for the dopamine D 4 receptor ligand, quinpirole, which is a full agonist in cAMP studies but a partial agonist as revealed by GTP␥[ 35 S] assays using the same transfected cells (Gazi et al, 2000). Our GTP␥[…”
Section: Discussionsupporting
confidence: 84%
“…6, C and D; Table 2), through a lower maximum response rather than a decrease in potency, which can be difficult to interpret. A similar discrepancy has been reported for the dopamine D 4 receptor ligand, quinpirole, which is a full agonist in cAMP studies but a partial agonist as revealed by GTP␥[ 35 S] assays using the same transfected cells (Gazi et al, 2000). Our GTP␥[…”
Section: Discussionsupporting
confidence: 84%
“…at ASPET Journals on May 7, 2018 jpet.aspetjournals.org sion of G␣ o , consistent with previous reports documenting poor coupling (Gazi et al, 2000). Constitutive internalization of the receptor has been proposed to explain the poor coupling observed with D 4 (Oldenhof et al, 1998 (Jardemark et al, 2002); however, the data presented above suggest that D 4 does not mediate the therapeutic effects of antipsychotic medications nor does selectivity for D 4 predict atypicality, in agreement with previous results (Roth et al, 1995).…”
Section: Intrinsic Efficacy Of Antipsychotics 1283supporting
confidence: 91%
“…However, a comprehensive efficacy profile of compounds that target D 2 -like receptors is lacking. The impact of inverse agonism upon the clinical properties of these compounds is not fully understood, in part because the low sensitivity of many functional assays prevents reliable measurements of constitutive activity, and precludes functional assessment of receptors that signal poorly in heterologous systems such as D 3 (see Newman-Tancredi et al, 1999) and D 4 receptors (see Oldenhof et al, 1998;Gazi et al, 2000). Previously, we have shown that overexpression of G-proteins increases assay sensitivity and induces constitutive activity of GPCRs (Burstein et al, 1997).…”
mentioning
confidence: 99%
“…hD 4 Receptors. In line with studies of CHO cells expressing the hD 4.2 isoform (Gilliland and Alper, 2000) and of cloned, rat D 4 sites (Gazi et al, 2000), quinpirole showed substantial efficacy at hD 4 (hD 4.4 ) receptors. This characteristic was shared by quinerolane and TL99.…”
Section: Discussionsupporting
confidence: 53%
“…This characteristic was shared by quinerolane and TL99. The agonist properties of pergolide, apomorphine, talipexole, and pramipexole at hD 4 sites complement work using other measures of drug efficacy and/or other hD 4 isoforms (Mieurau et al, 1995;Coldwell et al, 1999;Gazi et al, 2000;Gilliland and Alper, 2000). Like pergolide, two other ergolines, cabergoline and lisuride, similarly showed agonist properties at hD 4 sites.…”
Section: Discussionmentioning
confidence: 77%